Respuesta :

Answer:

x = 3

x = -5

Step-by-step explanation:

(9)(x+1)(x+1) = 144

(9)(x²+2x+1) = 144

9x²+18x+9 = 144

9x²+18x = 135

x²+2x = 15

x(x+2) = 15

x = 3

x= -5

Answer: [tex]x_1=3\\x_2=-5[/tex]

Step-by-step explanation:

Divide boht sides of the eqeuation by 9:

[tex]\frac{9(x+1)^2}{9}=\frac{144}{9}\\\\(x+1)^2=16[/tex]

Remembert that:

[tex](a+b)^2=a^2+2ab+b^2[/tex]

Then, applying this, you get:

[tex]x^2+2(x)(1)+1^2=16\\x^2+2x+1=16[/tex]

Subtract 16 from both sides:

[tex]x^2+2x+1-16=16-16\\x^2+2x-15=0[/tex]

Factor the quadratic equation. Find two numbers whose sum be 2 and whose product be -15, then:

[tex](x-3)(x+5)=0\\x_1=3\\x_2=-5[/tex]